SMARTPHONE VIDEO RECORDING AS A LEARNING TOOL TO IMPROVE INDONESIAN EFL STUDENTS SPEAKING PERFORMANCE - Dzakiah Dzakiah; Muhammad Azwar Assiddiq; Sri Hariati Mustari (Universitas Kuningan, 2020)
This research attempts to reveal the effectiveness of using smartphone video recording as an English learning tool to improve the students speaking performance and the students interest in using the tool in speaking learning process. All participants were second-grade students of private boarding school in Makassar, Indonesia. This research was conducted through quasi experimental study design with two groups comprises of 25 students in the experimental group and 25 students in the control group. The instruments were speaking test to collect the data about the students speaking performance and questionnaire to find out the students interest. The data collections were then analyzed through descriptive and inferential statistics through SPSS Program Version 23.0. The result of data analysis showed that (1) using smartphone video recording was more effective than in-class monologue presentation to improve the students performance in speaking. It is seen from the significance t test result that reveals the significance value is lower than the significance level; 0.005 <0.05. Furthermore, in relation to the students interest in using smartphone video recording to learn speaking and (2) it was found that the students interest in using smartphone video recording was categorized as high. Keywords: Smartphone video recording; speaking performance; interest.